2017
DOI: 10.1080/24699322.2017.1389397
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer histology image identification method based on texture and lesion area features

Abstract: The issue of an automated approach for detecting cervical cancer is proposed to improve the accuracy of recognition. Firstly, the cervical cancer histology source images are needed to use image preprocessing for reducing the impact brought by noise of images as well as the impact on subsequent precise feature extraction brought by irrelevant background. Secondly, the images are grouped into ten vertical images and the information of texture feature is extracted by Grey Level Co-occurrence Matrix (GLCM). GLCM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…The main problem in this approach is over-segmentation problems [24]. In feature extraction, mostly used features are shape [25], texture [26], and color features. The major advantage of using texture attribute is its simplicity.…”
Section: Methodsmentioning
confidence: 99%
“…The main problem in this approach is over-segmentation problems [24]. In feature extraction, mostly used features are shape [25], texture [26], and color features. The major advantage of using texture attribute is its simplicity.…”
Section: Methodsmentioning
confidence: 99%
“…3 Cervical cancer is one of the most preventable forms of cancer. There has also been significant improvement in screening, 4-8 diagnosis, [9][10][11] treatment, [12][13][14][15] and even chemoprevention [16][17][18] for cervical cancer. In the past decade, much effort has been made in China to reduce the burden of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Игор Пантић 1,2 , Драга Димитријевић 3 , Ивана Сташевић-Карличић 3 , Марта Јеремић 1 , Ана Старчевић 4 , Синиша Ристић 5 , Агата Блахнио 6 , Анета Прзепиорка 6 1 Универзитет у Београду, Медицински факултет, Институт за медицинску физиологију, Београд, Србија; 2 Универзитет у Хаифи, Хаифа, Израел; 3 Клиника за психијатријске болести "Др Лаза Лазаревић", Београд, Србија; 4 Универзитет у Београду, Медицински факултет, Институт за анатомију "Нико Миљанић", Београд, Србија; 5 Универзитет у Источном Сарајеву, Фоча, Република Српска, Босна и Херцеговина; 6 Католички универзитет "Јован Павле II", Лублин, Пољска…”
Section: Conflict Of Interest: None Declaredunclassified
“…Textural parameters of tissue architecture were shown to be a potentially important addition to conventional cell biology and histology methods [5,6]. For example, in a study published in 2009, Shamir and associates demonstrated that these features, when calculated on muscle tissue in an animal experimental model, can be a possible indicator of structural deterioration during physiological aging.…”
Section: Introductionmentioning
confidence: 99%